Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am stuck when it comes to finding the end value of a trig function. I have the following question:

$$ \tan^5x - 9\tan{x} = 0 $$

I worked the problem and got:

$$ \tan x = 0\\ \tan^4x-9 = 0\\ x = 0, \pi, \frac {\pi}{3}, \frac {2\pi}{3}, \frac {4\pi}{3}, \frac {5\pi}{3} $$

My book answer is $x = \frac {\pi k}{3}$ how do you get that? I understand that tan uses $ \pi $ and sin, cos use $ 2\pi $ but I'm not sure how they got to that answer.

share|improve this question
    
Could you also state the domain of $k$? Eg. $k = 2, 4, 6, ...$. –  bryansis2010 Feb 13 '13 at 5:01
2  
Look at the answers you got. Are they not all of the form $\pi k/3$, for various values of $k$? –  Gerry Myerson Feb 13 '13 at 5:04
add comment

3 Answers 3

up vote 2 down vote accepted

$$\tan^4x=9\Longrightarrow \tan^2x= 3\Longrightarrow \tan x=\pm\sqrt 3=\pm\frac{\frac{\sqrt 3}{2}}{\frac{1}{2}}=\pm\frac{\sin\frac{\pi}{3}}{\cos\frac{\pi}{3}}$$

Can you see it now?

share|improve this answer
add comment

You made an error in your work. e.g. when you solved $\tan x = 0$, you only found the two solutions $0$ and $\pi$. But you missed all of the other solutions like $2 \pi$, $3 \pi$, and $-1872 \pi$. The set of all solutions to $\tan x = 0$ is the set of all values $\pi v$ where $v$ ranges over all integers.

share|improve this answer
add comment

$\tan^2x=3\implies \cos2x=\frac{1-\tan^2x}{1+\tan^2x}=\frac{1-3}{1+3}=-\frac12=\cos\frac{2\pi}3$

$2x=2n\pi\pm \frac{2\pi}3=\frac{2\pi}3(3n\pm1)$ where $n$ is any integer.

$x=\frac{\pi}3(3n\pm1)$

Now, we need $0\le \frac{\pi}3(3n+1)<2\pi\implies 0\le3n+1<6\implies n=0,1$

For $n=0, x=\frac{\pi}3(3n+1)= \frac{\pi}3; n=1\implies x=\frac{\pi}3(3n+1)= \frac{4\pi}3$

Similarly, we need $0\le \frac{\pi}3(3n-1)<2\pi\implies 0\le3n-1<6\implies n=1,2$

For $n=1, x=\frac{\pi}3(3n-1)= \frac{2\pi}3; n=2\implies x=\frac{\pi}3(3n-1)= \frac{5\pi}3$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.